THE VIABILITY OF HEMOLYTIC STREPTOCOCCUS IN CERTAIN SOLUTIONS CONTAINING GELATIN - Meleney, Frank L. (The Rockefeller University Press, 1924)
1. The findings of Robertson, Sia, and Woo with regard to the preservative action of 0.1 per cent gelatin in suspending fluids for the pneumococcus have been confirmed for the streptococcus. 2. In gelatin-citrate, gelatin-Locke's, and gelatin-"20:1" solutions, the streptococcus will live for 3 days or longer at room temperature and for 12 hours or longer at incubator temperature in dilutions as high as 100 cocci per cc. 3. The gelatin in 0.1 per cent concentration maintains life at a fairly constant numerical level for from 15 to 24 hours. These fluids may therefore be used for certain quantitative biologic tests. 4. In slightly higher concentrations of gelatin, there is actual growth which suggests that even in 0.1 per cent concentrations the gelatin has a nutrient action. 5. There is also evidence that gelatin affords some protection against the mechanical injury of the dilution process. 6. The toxic action of unbalanced salts, the possible lytic action of water, and the autolytic action of the organisms themselves are all delayed by the presence of gelatin, but eventually these actions take place in the same manner that has been described before by many observers and as here observed for solutions without gelatin. 7. The life of streptococci is maintained in these gelatin solutions through a relatively wide zone of hydrogen ion concentration.